GPS-Enabled Blind Stick Using Ultrasonic Technology (International Journal of Innovative Research in Engineering & Management, 2024)
This paper presents a GPS tracking system  for an ultrasonic blind stick. People with visual impairments  have historically used sticks to detect obstructions in their  path. But the person using this stick has to deal with a  number of issues because it is inefficient in a number of  ways. Giving visually challenged people a better  navigational aid is the aim of this initiative. Thanks to the  use of sensors, object recognition is made easier with the  ultrasonic blind walking stick than with the regular walking  stick. The data on his present location is provided by his  GPS system.In the event that the blind person loses track of  where they put their stick, the system has an additional  sophisticated tool to assist them. Blind Stick the ultrasonic  blind stick with GPS tracking device is described in the  paper’s abstract. Historically, those who are blind or  visually challenged have utilized a stick to detect  obstructions in their path. However, there are a number of  inefficiencies with this stick, and the user must deal with a  number of issues. Better navigational aids for the blind and  visually handicapped are the aim of this study. Because it uses sensors to facilitate object identification, the  ultrasonic blind walking stick is far more sophisticated than  the conventional walking stick. Information about his present location is provided by his  GPS system. One other cutting-edge feature built into the  system will assist blind people in finding their stick in the  event that they misplace it.
Keywords: GPS-Enabled; Blind Stick; Ultrasonic Technology; Visually challenged